Spremembe v zemljiških kategorijah v Sloveniji - Vrišer, Igor (Geografski vestnik, 1987)
The article treats the changes in categories of land in Slovenia between 1900 and 1981. The sources and methods of data collecting are stated. The changes can be seen in four directions: areas of fields, fores and nonproductive land (greenswarding, aforestation, urbanization) are increasing. The process has began after the second World war befor that, relations between categories of land were relatively stable.
Keywords: 1900-1981; categories of land; geografija; geography; Slovenia; Slovenija; zemljiške kategorije